Organizational Citizenship Behavior Predicts Quality, Creativity, and Efficiency Performance: The Roles of Occupational and Collective Efficacies - Yaakobi, Erez; Weisberg, Jacob (Frontiers in Psychology, 2020)
Although numerous studies have shown that prosocial behavior impacts performance within organizations, the mechanisms that encourage or discourage these effects have rarely been explored. Two studies were conducted to shed light on the role of psychological beliefs on prosocial dynamics in predicting organizational performance. In Study 1, employees' beliefs in their inner job-related resources (Occupational Efficacy - OE) were examined as a predictor of OCB. It was posited that OE, which is an inner resource, should positively predict OCB. Study 2 examined whether Collective Efficacy (CE), which is an external resource over which employees have less control, would moderate the OCB-performance prediction. Overall, performance and three core dimensions of performance (quality, creativity and efficiency) were assessed to better capture the specific influence of OCB effects on performance. In Study 1 employees completed inventories measuring their OE, OCB and performance. In Study 2, employees completed inventories measuring their CE and OCB. In addition, their managers completed inventories measuring the CE of their employees’ teams and their employees' performance. The results of Study 1 revealed that OE emerged as an antecedent of OCB in predicting performance. In Study 2, OCB positively predicted employee performance above and beyond and the effects of their managers' tenure in position, and CEs. In addition, both employees' and managers' CEs moderated the effects of OCB on performance: the performance effects of OCB increased as employees’ and managers’ CE increased, and specifically performance efficiency and performance creativity. These findings contribute to a better theoretical and practical understanding of the core factors that affect the organizational dynamics of prosocial behaviors that can lead to higher performance and the ways in which OCB positively predicts performance in organizational settings.